Transportation Engineering Revolution: Towards Sustainable and Intelligent Mobility - Jixiong, Cai; Wang, Yuanyuan; Zou, Guijiao (Journal of Moeslim Research Technik, 2024)
The revolution in the field of transportation engineering has been a major highlight in efforts towards achieving more sustainable and intelligent mobility. This development is triggered by increasing awareness of the negative impacts of traffic congestion and air pollution on society’s quality of life and the environment. This research aims to investigate and identify innovative solutions to address existing transportation problems, focusing on developing more efficient, environmentally friendly, and sustainable transportation systems. The approach used in this research is a comprehensive analysis of recent developments in transportation technology and case studies to evaluate the implementation of proposed solutions. Based on the analysis, the research results show that the development of transportation technology based on renewable energy, the application of artificial intelligence in traffic management, and the promotion of efficient public transportation are critical steps in achieving sustainable and intelligent mobility. The conclusion of this research emphasizes the importance of adopting innovative solutions in addressing modern transportation challenges. We can build transportation systems that promote more sustainable, efficient, and environmentally friendly mobility by leveraging the latest technology and implementing appropriate policies.